HIV self-test reporting using mHealth platforms: A pilot study in Johannesburg, South Africa - Phatsoane Gaven, Mothepane; Quaife, Matthew; Majam, Mohammed; Singh, Leanne; Rhagnath, Naleni; Wonderlik, Theodore; Gumede, Siphamandla Bonga (Frontiers in Reproductive Health, 2023)
Background The main impediment to operational scale-up of HIV self-testing (HIVST) and counselling, is a dearth of information on utilisation, reporting, and linkage to care for HIV-positive individuals. To inform solutions to this issue, this study investigated the utility of self-testers reporting their results using a mobile-health (mHealth) platform, and whether seropositive users linked into care. Method Candidates who met the recruitment criteria across multiple sites within inner-city Johannesburg each received an HIVST kit. Using short message service (SMS) reminders (50% standard and 50% behavioural science), participants were prompted to self-report results on provided platforms. On the seventh day, users who did not make contact, were called, and surveyed via an interactive voice response system (IVRS). Multivariable regression was used in reporting by age and sex. Results Of the 9,505 participants, 2,467 (25.9%) participants answered any survey question, and of those, 1,933 (78.4%) were willing to self-report their HIV status. Men were more likely than women to make an inbound call (10.2% vs. 9.1%, p = 0.06) however, women were significantly more likely to self-report their test result (AOR = 1.12, 95%CI = 1.01–1.24, p = 0.025). Overall, self-reporting a test result was predicted by being younger and female. In addition, reporting HIV results was associated with age, 25–35 (AOR = 1.58, 95% CI = 1.24–2.02) and above 35 years (AOR = 2.12, 95% CI = 1.61–2.80). Out of 1,933 participants willing to report their HIV status, 314 reported a positive test, indicating a HIV prevalence of 16.2% (95% CI: 14.6%–18.0%) and of those 204 (65.0%) reported inclination to link to care. Conclusion While self-reporting HIVST results via an IVRS system yielded a higher response rate, behavioural SMSs were ineffective in increasing self-reporting.